Resources and Resourcefulness : Gender, Conflict, and Artisanal Mining Communities in Eastern Democratic Republic of the Congo - World Bank (Washington, DC, 2015)
Recent studies in the DRC tend to focus on human rights abuses or on the status of women, however few investigations examine the link between mining and sexual violence. There is a dearth of research specifically into the gender dimensions of artisanal and small-scale mining (ASM) as a means to economic security for both men and women. Further, there has been insufficient analysis of the real and potential threats to women’s human rights in the artisanal mining sector in DRC. Once these threats are identified, governmental and other partners can be informed as to protective and restorative actions they can take to assure the rights of vulnerable groups within mining communities. With improved understanding of the vulnerabilities, opportunities, and human rights threats facing women in conflict-affected small-scale mining areas, governmental and NGO partners can be better informed both how to prevent violations of rights, as well as how to promote rights and improve economic and social outcomes for women and communities. The ASM sector has been noted as a significant element in the ongoing conflict in DRC, with particularly negative implications for women, but also has the potential to lead to considerable economic gains. The objectives of the study will be to: (i) identify the key gender dimensions of ASM in the Kivus, particularly in terms of how conflict exacerbates or changes what is already known about the gender dimensions of ASM and to understand the human rights issues facing women; (ii) identify specific sources of gendered vulnerability to human rights abuses within AMS communities and identify ways to address these vulnerabilities; and (iii) identify methodologies of resilience or positive coping in communities.